2010
DOI: 10.1017/s1461145710000106
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of GABAA receptor in the molecular mechanisms of combined selective serotonin reuptake inhibitor-antipsychotic treatment

Abstract: There is evidence that combining selective serotonin reuptake inhibitor (SSRI) antidepressant and antipsychotic drugs may improve negative symptoms in schizophrenia and resistant symptoms in obsessive-compulsive and affective disorders. To examine the mechanism of action of this treatment we investigated the molecular modulation of γ-aminobutyric acid-A (GABA(A)) receptor components and biochemical pathways associated with GABA(A) receptor function following administration of the SSRI fluvoxamine (Flu) combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…The effect of chronic HALO-FLU combined treatment on GABA-A Rβ2/3 receptor in rat PFC Acute studies in our laboratory showed that HALO-FLU combined affected GABA-A receptors differently than each drug given alone (Danovich et al 2011;Chertkow et al 2006). Figure 1 shows the effect of chronic treatment on the GABA-Aβ2/3 receptor expression levels and cellular distribution in rat PFC.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of chronic HALO-FLU combined treatment on GABA-A Rβ2/3 receptor in rat PFC Acute studies in our laboratory showed that HALO-FLU combined affected GABA-A receptors differently than each drug given alone (Danovich et al 2011;Chertkow et al 2006). Figure 1 shows the effect of chronic treatment on the GABA-Aβ2/3 receptor expression levels and cellular distribution in rat PFC.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of chronic HALO-FLU combined treatment on PKC and ERK2 phosphorylation in rat PFC Next, we examined changes in the activation of MAPK/ ERK signaling pathways, as PKC and ERK2 are known to be involved in the regulation of GABA-A receptor and might be influenced by psychotropics (Danovich et al 2011). It is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations